2021
DOI: 10.1155/2021/6683148
|View full text |Cite
|
Sign up to set email alerts
|

Single Immunoglobulin IL-1-Related Receptor (SIGIRR) Gene rs7396562 Polymorphism and Expression Level in Rheumatoid Arthritis

Abstract: Objectives. The aim of our study was to investigate the association of single-nucleotide polymorphism (SNP) and mRNA expression profile of single immunoglobulin IL-1-related receptor (SIGIRR) in rheumatoid arthritis (RA) in a Chinese population. Methods. SIGIRR rs7396562 polymorphism was genotyped using TaqMan allelic discrimination assay in 517 RA patients and 601 healthy controls. Simultaneously, the SIGIRR mRNA expression levels of 79 RA patients and 76 healthy controls were examined by real-time quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An association was uncovered between IL-1R8 expression level and dog breed, which could be related to specific polymorphisms of the gene in different populations of dogs [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…An association was uncovered between IL-1R8 expression level and dog breed, which could be related to specific polymorphisms of the gene in different populations of dogs [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Memory CD4 T cells are of great interest in the context of autoimmune diseases because of their long-lived nature, efficient responses to antigens, and unique potential to mediate recurring autoimmune responses (Raphael et al 2020). Based on the relatively higher expression of the SIGIRR gene on human memory CD4 T cells or CD4 T cells predicted by single-cell or bulk transcriptomic analysis, memory CD4 T cells were focused on demonstrating the functions of SIGIRR in RA, although gene polymorphisms and the regulation of SIGIRR in rheumatoid arthritis have been reported in earlier studies (Drexler et al 2010;Yang et al 2021). We observed an aberrant downregulation of SIGIRR and enhanced TNF-α production in memory CD4 T cells from the peripheral blood of RA patients and found that SIGIRR deficiency promoted the progression of AIA mediated by elevated TNF-α expression, thus establishing a closer association between SIGIRR and TNF-α production in memory CD4 T cells in RA for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HDAC mRNA might play an essential role in the pathogenesis of RA ( 68 ). The single immunoglobulin IL-1-related receptor (SIGIRR) mRNA expression was decreased in the PBMCs of RA patients in a study including 79 such patients, and SIGIRR dysregulation might be related to RA pathogenesis and susceptibility ( 69 ). In a recently published study of 650 patients with RA, signaling lymphocyte activation molecule family 6 (SLAMF6) expression in the synovial tissue was 1.6-fold higher than in the controls and correlated with the severity and susceptibility of RA ( 70 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%